Recent Advances in Cardiovascular Magnetic Resonance: Techniques and Applications. (June 2017) - Salerno, Michael; Sharif, Behzad; Arheden, Håkan; Kumar, Andreas; Axel, Leon; Li, Debiao; Neubauer, Stefan
Abstract : Cardiovascular magnetic resonance imaging has become the gold standard for evaluating myocardial function, volumes, and scarring. Additionally, cardiovascular magnetic resonance imaging is unique in its comprehensive tissue characterization, including assessment of myocardial edema, myocardial siderosis, myocardial perfusion, and diffuse myocardial fibrosis. Cardiovascular magnetic resonance imaging has become an indispensable tool in the evaluation of congenital heart disease, heart failure, cardiac masses, pericardial disease, and coronary artery disease. This review will highlight some recent novel cardiovascular magnetic resonance imaging techniques, concepts, and applications.